On the Forms гуля́ле, nашле́ ‘we, they walked, went away’ etc. in Pskovian Vernaculars Near Opočka - Чекмонас, Валерий (Slavistica Vilnensis, 2002)
Careful analysis of tape recordings made in the above vernaculars in MayJune 2002 revealed an interesting phenomenon not detected previously by dialectologists: the high vowels [i y u] and the medial [e] are more open and lower in post-tonic final open syllables (-CV) which are intonationally strong (in words under emphasis and in absolute final position). The unaccented vowels in these syllables are long and loud in volume, and change their quality from [i y u e] to [e э о ’э]; being realized under stress as broadening diphthongs (or diphthongoids). For example, instead of xaди́ли ‘they walked’, де́ньги ‘money’, Со́кълъвы (Со́коловы, family name), бо́гу (Dat. Sg. from бог ‘God’), ве́илку (Sg. Dat. from веялка ‘winnowing-machine’), хо́де (‘he/she walks’, the 3rd Sg. Praes. from ходи́ть ‘to walk’) in intonationally neutral position the same words are pronounced хади́ли, де́ньге, Со́кълъвэ, бо́го, ве́илко, хо́дя when they are in strong position. In connection with this phenomenon, the article also discusses briefly the mysterious ending [-e] (in Nom. Sg. masc of substantives and in the 3rd Sg. Praet.).